2008
DOI: 10.1007/s00421-008-0683-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of AMPD1 genotype on blood flow response to sprint exercise

Abstract: Inherited deficiency of skeletal muscle myoadenylate deaminase (mAMPD) is a genetic disorder characterized primarily by a 34C>T transition in exon 2 of the AMPD1 gene. mAMPD deficient individuals exhibit alterations in ATP catabolic flow, resulting in greater adenosine accumulation during high intensity exercise that may possibly enhance exercise-induced hyperaemia. This study tested the hypothesis that individuals with diminished mAMPD activity due to mutations in the AMPD1 gene develop a greater and faster b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…A null TT genotype and low T unaffected by AMPD1 genotypes [13]. In contrast, a faster power decrease and a lower mean power was demonstrated in individuals with TT and CT genotypes during the 30 s cycling test [27].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A null TT genotype and low T unaffected by AMPD1 genotypes [13]. In contrast, a faster power decrease and a lower mean power was demonstrated in individuals with TT and CT genotypes during the 30 s cycling test [27].…”
Section: Discussionmentioning
confidence: 91%
“…The CC genotype and C allele are considered to be related to performance in power-oriented athletes, and T allele might be a negative factor for athletic performance [29]. However, it was reported that high intensity anaerobic performance was not influenced by AMPD1 genotypes [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMPD1 is preferentially expressed at high levels in type II skeletal muscle, where it influences the levels of inorganic phosphate, AMP, ADP, and phosphocreatine (Coley et al, 2012). Patients with an inherited defect in AMPD1 expression often have significantly decreased muscle performance, suggesting that the purine nucleotide catabolic pathway plays a role in short-term energy production (Fischer et al, 2007;Norman et al, 2008). The AMPD1 gene is highly expressed in skeletal muscle, and is involved in the rate-limiting step of the purine nucleotide cycle, allowing repletion of ATP stores.…”
Section: Introductionmentioning
confidence: 99%